Characterization and enhanced performance of Ivorian clays as potential modifiers in carbon paste electrodes - Legré Paul Gauly; Mariame Coulibaly; Ségnéninhinténin Bakary Soro; Koffi Siméon Kouadio; Seiny Roger N’Dri; Ali Sanou; Albert Trokourey (Discover Applied Sciences)
Abstract To address the challenge of developing new materials for electrochemical sensors, this study focused on two Ivorian clays, MO and TS, traditionally used in pottery. The objective was to evaluate their potential as modifiers for carbon paste electrodes. The clays underwent physicochemical and electrochemical characterizations, including density measurements, X-ray diffraction, thermogravimetric analysis, differential thermal analysis, specific surface area, Fourier-transform infrared spectroscopy, scanning electron microscopy, X-ray fluorescence and cation exchange capacity. Our analyses revealed that these clays are primarily composed of kaolinite, quartz, illite, and goethite. In addition, to enhance the properties of the clay, sodium ions were successfully incorporated into clays, resulting in higher sodium content and an increased specific surface area. These sodium-saturated clays (MO-Na and TS-Na) were then used to modify carbon paste electrodes. Performance evaluation using cyclic voltammetry with a ferri/ferrocyanide redox marker showed that electrodes modified with 10% MO-Na exhibited significantly enhanced sensitivity compared to unmodified counterparts. This study underscores the potential of sodium-saturated Ivorian clays to enhance the performance of electrochemical sensors.